Analisis Pengetahuan Orang Tua Terhadap Pentingnya Menjaga Kesehatan Mental Anak Pada Perilaku Bullying Siswa - Farah Azizah; Yamin Yamin (Universitas Negeri Makassar, 2023)
The reasons why children do bullying are individual factors such as temperament, family factors, peers, school environment and social media. Children who do bullying behavior are not known by their parents, for reasons of fear of being scolded when their parents find out. Parents, when punishing their naughty children, often punish them physically, whether it's being hit or slapped, so that when this happens often the child becomes more violent in their environment and can result in the child bullying his friends. The purpose of this research is to describe bullying behavior towards elementary school children. The research method uses interviews and observations of 4 grade III students, consisting of 2 (two) students who are the target of bullying and 2 (two) students who are bullies at school. bullying occurs at school and outside of school. Pay attention to the child's environment when hanging out, because it will have an impact on the way the child behaves and speaks to others.